Exploring the Role of Teacher Scaffolding in Fostering Independent Learning - Maisarah, Syarifah; Motevalli, Saeid (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to explore how teacher scaffolding practices contribute to the development of independent learning among students in Malaysia. A qualitative research design was employed using semi-structured interviews with 25 teachers from secondary schools and higher education institutions across Malaysia. Participants were selected through purposive sampling, ensuring diversity in subject areas and teaching experience. Data collection continued until theoretical saturation was achieved. Interviews, lasting 45–60 minutes, were audio-recorded, transcribed verbatim, and analyzed using thematic analysis with NVivo 14 software. Coding followed an iterative process to identify open codes, subthemes, and overarching themes. Trustworthiness was enhanced through peer debriefing and reflective memoing. Four major themes emerged from the analysis. First, teachers reported diverse instructional scaffolding strategies, including guided questioning, modeling, chunking, feedback, gradual release of responsibility, and differentiated support. Second, scaffolding was found to promote learner autonomy by fostering reflection, decision-making, self-regulation, peer collaboration, and intrinsic motivation. Third, teachers emphasized socio-emotional support such as building trust, encouragement, creating safe learning climates, empowering confidence, addressing anxiety, and cultural sensitivity as integral to fostering independence. Finally, participants identified challenges and conditions of scaffolding, including time constraints, large class sizes, variability in student readiness, limited resources, exam pressures, and sustainability of independence. Collectively, these findings illustrate scaffolding as a multidimensional process combining cognitive, motivational, and socio-emotional dimensions. The study demonstrates that teacher scaffolding plays a pivotal role in facilitating independent learning by integrating instructional, motivational, and relational strategies. However, systemic and contextual barriers, such as curriculum pressures and limited resources, can constrain its effectiveness. The findings underscore the need for professional development, institutional support, and policy initiatives to strengthen scaffolding practices and ensure their sustainability in fostering lifelong independent learners.